Pigs Like It Varied; Feeding Behavior and Pre- and Post-weaning Performance of Piglets Exposed to Dietary Diversity and Feed Hidden in Substrate During Lactation - Middelkoop, Anouschka; van Marwijk, Manon A.; Kemp, Bas; Bolhuis, J. Elizabeth (Frontiers in Veterinary Science, 2019)
Timely intake of solid feed is essential to ease the nutritional change from sow’s milk to solid feed at weaning and thereby to reduce weaning-related problems. A significant percentage of piglets, however, do not or hardly consume solid feed before weaning. We studied effects of dietary variety and presenting the feed in substrate during lactation on the feeding behavior and performance of piglets up to two weeks post-weaning. Feed was provided ad libitum from d4 in two feeders, with four bowls each. In a 2x2 arrangement, forty litters received either creep feed as a monotonous diet (MO) or four feed items simultaneously, i.e. creep feed, celery, cereal honey loops and peanuts, as a diverse diet (DD) and the feed was either provided without (CON) or with substrate (SUB), i.e. sand, in one of the two feeders up to weaning. Dietary diversity highly stimulated feed exploration and eating (≥2.5 times), feed intake and the percentage of (good) eaters from early in lactation, and enhanced piglet growth towards weaning (by 29 g/d), although MO-piglets spent more time eating creep feed from d18. Within MO, SUB-litters consisted of more good eaters than CON-litters. At weaning (d28) four piglets from the same treatment were grouped (n=40 pens). DD-CON had the highest post-weaning feed intake and gain between d5-15 and the lowest proportion of pigs with higher tail damage scores. However, effects regarding behavior remained inconclusive, as DD-piglets had a lower and higher number of body lesions at 4 h and d15 post-weaning respectively, spent less time exploring the feed(er) and drinker and environment, and more time nosing pen mates than MO-piglets. SUB-piglets showed a reduction in total post-weaning feed intake, gain (particularly between d0-2) and inactivity, increased levels of manipulation and aggression at week 1 and a higher number of body lesions at 4 h and d15 post-weaning. In conclusion, dietary diversity seems a promising feeding strategy in getting piglets to eat during lactation. Provision of substrate in the feeder subtly stimulated foraging behavior, but negatively impacted post-weaning adaptation, probably because treatments were not reinforced after weaning and piglets thus experienced loss of enrichment.